Assessment of Pennisetum purpureum clones obtained by in vitro tissue culture - Herrera, Rafael Segundo; Garc?a, M.; Romero, Aida (Cuban Journal of Agricultural Science, 2012)
The performance of some agronomic indicators of 12 new Pennisetum purpureum clones (14, 18, 19, 20, 21, 24, 30, 36, 39, 41, 42 and 43) obtained by in vitro tissue culture was assessed during a year and they were compared to their progenitor (P. purpuereum vc. Cuba CT-115) through a completely random design with four repetitions. Plots of 25m2, without irrigation and fertilization, were used. The samplings were conducted every 60 and 90 d in the rainy and dry seasons, respectively. There were differences (P < 0.001) in the clones? height, but none of them surpassed the control (67.9 cm) in the rainy season, while the 14, 18, 20, 30 and 36 highlighted in dry season (P < 0.001). Similar performance was recorded for the leaves? length during the rainy season. The highest (P < 0.001) width was for the clones 39 (3.7cm) and 43 (3.1cm) in the rainy and dry seasons, respectively. The highest (P < 0.001) leaves percentages were reached by the clones 41 and 43 (65.8 and 66.1 %, respectively) in the rainy season and the 39, 41 and 43 (53.5; 53.1 and 54.8 % respectively) in the dry season. The clone 20 recorded the highest (P < 0.001) total yield (14.9 tDM/ha/year), but only produced the 28.2 % in the dry season. This clone also had the highest population (17.6 bunch/5m) at the end of the experiment. There are new clones of P. purpureum with favorable productive characteristics increasing the available gene-fund of this species, mainly the clone 20 that surpassed the control in the yield, content of leaves and population. Basic studies to explain the differences found between clones are necessary, as well as the study of their responses when using maintenance fertilization. Key words: Pennisetum purpureum, clones, agronomic indicators, yields.